Whistleblowing System Mempengaruhi Kepatuhan Wajib Pajak Di Indonesia: Apakah Risiko Sanksi Pajak Memoderasi? - Kahfi Fikrianoor; M. Rizki Utama; Faishal Prahatma Ganinda; Agung Dwi Nugroho; Amir Hidayatulloh (Institut Ilmu Sosial dan Manajemen STIAMI, 2020)
The purpose of this research was to determine the effect of whistleblowing system and sanction risk on taxpayer compliance. in addition, this research aims to determine whether the sanctions risk variable moderates between the whistleblowing system to taxpayer compliance in Indonesia. The population in this research is taxpayers in Indonesia. The sample in this research is an individual taxpayer residing in Indonesia. Sampling in this research using convenience sampling. The data collection of this research used a survey method with the help of a questionnaire distributed via Google forms. This research obtained 104 respondents. Data analysis techniques in this research used Partial Least Square with the help of WarpPLS. This research found that tax compliance in Indonesia is influenced by the Whistleblowing system and the risk of tax sanctions. However, the risk of tax sanctions cannot moderate the effect of the whistleblowing system on tax compliance in Indonesia